Association between tuberculosis and circulating microRNA hsa-let-7b and hsa-miR-30b: A pilot study in a Chinese population. (July 2016) - Xin, Henan; Yang, Yu; Liu, Jianmin; Li, Xiangwei; Li, Mufei; Feng, Boxuan; Li, Zhen; Zhang, Haoran; Li, Hengjing; Shen, Fei; Guan, Ling; Gao, Lei
Summary: Tuberculosis remains one of the world's deadliest communicable diseases. Limitations in the current diagnosis tools have heavily slowed down the step to eliminate TB. The objective of this study was to identify potential circulating miRNA associated with tuberculosis (TB) infection and disease development. Agilent human miRNA microarray was used to estimate the circulating levels of 1887 miRNAs among 34 study participants (10 patients with pulmonary TB, 13 controls with latent TB infection and 11 non-infected healthy controls). The identified miRNAs were subsequently verified by real-time qPCR. Target gene prediction and miRNA-gene network construction were further explored. A total of 119 miRNAs were identified to be in different levels between any two groups of the study population by microarray (Fold Change>2, p < 0.01). 11 most promising miRNAs were then selected for verification by real-time qPCR. The levels of hsa-let-7b-5p and hsa-miR-30b-5p were confirmed to be significantly up-regulated in pulmonary TB patients as compared to both control groups (p < 0.01). Caspase 3 was predicted to be one common target gene for these two miRNAs. None of the selected miRNA was confirmed to be related with the infection status. This pilot study suggested circulating hsa-let-7b and hsa-miR-30b might be associated with TB development by regulating the target genes involved in TLR-NF-kB mediated signal pathway.